Analyzing the Term Structure of Interest Rates using the Dynamic Nelson-Siegel Model with Time-Varying Parameters - Siem Jan Koopman; Max I.P. Mallee; Michel van der Wel (Tinbergen Institute, 2007)
In this discussion paper we introduce time-varying parameters in the dynamic Nelson–Siegel yield curve model for the simultaneous analysis and forecasting of interest rates of different maturities. The Nelson–Siegel model has been recently reformulated as a dynamic factor model with vector autoregressive factors. We extend this framework in two directions. First, the factor loadings in the Nelson–Siegel yield model depend on a single loading parameter that we treat as the fourth latent factor. Second, we specify the overall volatility as a generalized autoregressive conditional heteroscedasticity (GARCH) process. We present empirical evidence of considerable increases in within-sample goodness of fit for these advances in the dynamic Nelson–Siegel model.
Keywords: C32; C51; E43; 330; Yield Curve; Time-varying Volatility; Spline Functions; Kalman Filter; Missing Values; Zinsstruktur; Dynamisches Modell; Zustandsraummodell; Theorie